Simulacra and spectacle: The role of negative public values in the re-enchantment of U.S. politics. Issue 4 (2nd October 2021) - Smith-Walter, Aaron; Angelucci, Christian
Abstract: This paper details the manner in which Trump's brand image and use of political spectacle attempt to displace political authority reliant on rationality in decision making, which has long legitimated public bureaucracy. The corresponding threat to contemporary governance arrangements has undermined the sense of stability, and this paper examines Trump's use of media spectacle to exploit neoliberal administration's inability to appreciate aspects of the human condition outside of abstracted modeling, as detailed by Baudrillard's concept of simulation. We argue that this weakness in contemporary public bureaucracy is tied to a reticence to acknowledge and confront the animating role of negative public values in public administration in the U.S. We argue that Trump's brand image filled this vacuum by providing a counterweight to a public bureaucracy unable to convince citizens of its commitment to the common good.